Unravelling the working junction of aqueous-processed polymer–nanocrystal solar cells towards improved performance. Issue 23 (27th May 2016) - Chen, Zhaolai; Du, Xiaohang; Jin, Gan; Zeng, Qingsen; Liu, Fangyuan; Yang, Bai
Abstract : We demonstrate that the working principle of hybrid solar cells based on water-soluble polymers and nanocrystals follows a p–n junction instead of a type-II heterojunction. An improved PCE of 5.41% is obtained by optimizing these cells. Abstract : Hybrid solar cells (HSCs) based on aqueous polymers and nanocrystals are attractive due to their environmental friendliness and cost effectiveness. In this study, HSCs are fabricated from a series of water-soluble polymers with different highest occupied molecular orbital (HOMO) levels and nanocrystals with different Fermi levels. We demonstrate that the working principle of the aqueous-processed HSCs follows a p–n junction instead of a type-II heterojunction. The function of the polymer is to provide an interface dipole which can improve the build-in potential of the HSCs. Subsequently, the aqueous-processed HSCs are optimized following a p–n junction and an improved PCE of 5.41% is achieved, which is the highest for aqueous-processed HSCs. This study will provide instructive guidelines for the development of aqueous-processed HSCs.